Implementasi Sistem Kesehatan dan Keselamatan Kerja pada Penyulingan Minyak Atsiri Pujon Hill - Immanuel Mu'ammal; Uci Yuliati (Peradaban Journal of Community Service, 2025)
Occupational Health and Safety (OHS) is a crucial effort to create a safe and healthy work environment, aiming to minimize the risk of workplace accidents. This community service activity aims to improve the understanding and awareness of workers at the essential oil distillation facility in Pujon Hill regarding the implementation of OHS principles. The methods used include the dissemination of OHS concepts and the development of an OHS system adapted to local working conditions. The results show an increased understanding among workers about the importance of risk identification and the application of preventive measures in the workplace. This activity is expected to serve as a starting point for building a safer and more sustainable work culture. Kesehatan dan Keselamatan Kerja (K3) merupakan upaya penting dalam menciptakan lingkungan kerja yang aman dan sehat, guna meminimalkan risiko kecelakaan kerja. Kegiatan pengabdian ini bertujuan meningkatkan pemahaman dan pengetahuan para pekerja di penyulingan minyak atsiri Pujon Hill terkait penerapan K3. Metode yang digunakan meliputi sosialisasi prinsip-prinsip K3 dan pengembangan sistem K3 yang sesuai dengan kondisi kerja setempat. Hasil kegiatan menunjukkan adanya peningkatan pemahaman pekerja terhadap pentingnya identifikasi risiko dan penerapan langkah-langkah preventif di tempat kerja. Kegiatan ini diharapkan dapat menjadi awal dari pembentukan budaya kerja yang lebih aman dan berkelanjutan.